Menelisik Dorongan Agresi Para Pelajar Pelaku â€œKlithihâ€ di Yogyakarta - Sarwono, Budi (SOLUTION, Journal of Counseling and Personal Development, 2019)
This paper is a theoretical analysis of aggressive behavior of adolescent in Yogyakarta who has exceeded the limits of reasonableness. This aggression behavior culturally called "Klithih", has a significant increase in late 2016. The delinquency is often done without any reason, they beat,  burn and even kill their opponents. Dozens of student perpetrators "klithih" have been imprisoned as responsibility of their behavior, hundreds of them still awaiting their turn to be tried in court. People needs to solve this worrying behavior. This study is providing a theoretical perspective to follow-up, such as research, policy formulation, or formulate any interventions to address this phenomenon. This paper discusses trend of juvenile delinquency in around the worlds to describe the local phenomenon of "klithih" and various theoretical perspectives about it. Since "klithih" have very local meaning, so in this study, the psychocultural approach becomes an important focus. The final section of this paper deals with possible bids to handle juvenile delinquency.